Group portrait of the attendees of the 87th session of the California State Grange - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the 87th California State Grange, held November 9-12, 1959 at the Municipal Auditorium in Long Beach, California. The attendees are assembled out of doors, in front of a building decorated with large banners that read "Myron Floren of L. Welk's Orch. The Revelations and Tuttles Claude M. Sailhamer presents another Fabulous Musical Sun Nov. 15 2PM Free," and "Welcome National and California State Grange November 9-18, 1959."